Paramount studies in islam 1 - Aziz, Abdul (Paramount books Karachi, 2002)
An in-depth exploration of key Islamic concepts and teachings, aimed at fostering a strong foundational knowledge for students. It combines academic rigor with accessible language to appeal to learners of all ages.